A Randomized Controlled Trial of Balint Groups to Prevent Burnout Among Residents in China - Huang, Lei; Harsh, Jennifer; Cui, Haisong; Wu, Jiaxin; Thai, Jessica; Zhang, Xu; Cheng, Liming; Wu, Wenyuan (Frontiers in Psychiatry, 2020)
Introduction: Burnout is highly prevalent among residents and is associated with negative outcomes for patients, organizations, and physicians. Balint groups have been shown to be an effective strategy to alleviate physicians’ burnout. The purpose of this study was to examine the effectiveness and feasibility of Balint groups in reducing burnout among residents in training programs in China. Methods: 36 resident physicians in their first year of residency at a comprehensive hospital in China were randomly assigned to two groups. Physicians in the intervention group participated in 2 lectures and 10 Balint sessions for 6 months, while participants in the control group were placed on a waitlist for future Balint sessions. Participants completed burnout and job satisfaction measures pre and post-intervention. Results: Paired t-test results revealed that burnout subscale scores for emotional exhaustion (P=0.013) and depersonalization (P=0.020) for the intervention group were significantly decreased after Balint group participation compared to those of the control group. No significant differences were found in scores for personal accomplishment (p=0.318) and job satisfaction(p=0.716) between groups. All 18 participants in the test group reported that Balint groups were helpful and that they would be willing to attend future Balint sessions. Overall satisfaction with the Balint groups program was over 80%. Conclusion: Balint groups are an efficacious, feasible, standardized method of reducing resident physician burnout. Residency programs in China may benefit from including Balint groups in their residency training programs.